Pig slurry: effect on soil and K, Ca and Mg losses by water erosion (Revista de Ciências Agroveterinárias, 2023)
Pigg slurry (PS) is used as a fertilizer whose nutrients are lost through erosion and contaminate the environment if the manure is used inappropriately. The objective was to evaluate the effect of PS on soil and erosion, in a Alfisol soil. The treatments, 0; 50; 100; and 200 m³ ha-1 of PS were applied superficially after sowing once in each of the five crops, and in the straw of the last crop, totaling 0, 250, 500 and 1000 m³ ha-1, in oat (Avena strigosa), corn (Zea mays), turnip (Raphanus sativus L.) and soybean (Glycine max), and in oat residues. The simulated rain (65 mm h-1 and 75 minutes) was applied three times to corn and four times to turnip, soybeans, and residues, with a rotating arms simulator. Before and after the research, the content of K, Ca and Mg in the soil was determined. The rainfall applied at each moment made up a test (T). T1 occurred after the application of the PS and the other tests at intervals that varied between 14 and 70 days, depending on the weather. During the runoff, at five-minute intervals, runoff samples were collected to determine water losses and the content of K, Ca and Mg in the water. The PS did not influence the nutrient content in the soil. The content and total losses of nutrients were higher with 1000 m3 ha-1 of PS than in the absence of manure. With the increase in runoff, the content in the runoff decreased and the total loss increased, which also increased with the increase in the nutrient content in the runoff. It is recommended to apply less than 500 m3 ha-1 of total PS in the soil, even in interval applications, due to the high loss of K, Ca and Mg by water erosion.
Keywords: water erosion; nutrients in runoff; simulated rainfall; no-tillage; environment; nutrients; soil erosion